Hydrothermally constructed AgWO4-rGO nanocomposites as an electrode enhancer for ultrasensitive electrochemical detection of hazardous herbicide crisquat. (July 2022) - Maheshwaran, Selvarasu; Renganathan, Vengudusamy; Chen, Shen-Ming; Balaji, Ramachandran; Kao, C.R.; Chandrasekar, Narendhar; Ethiraj, Selvarajan; Samuel, Melvin S.; Govarthanan, Muthusamy
Abstract: The advancements in electrode materials with high efficiency has been prioritized to effectively monitor the presence of harmful pesticides concerning the environment. In such a way, we hydrothermally constructed a hybrid AgWO4 -rGO nanocomposites for the rapid electrochemical detection of crisquat (CQT). The structural, compositional, morphological and topographical characterization for AgWO4 -rGO nanocomposites is thoroughly performed to understand its electrocatalytic properties. The AgWO4 -rGO nanocomposites are used as an electrode enhancer (rGO@AgWO4 /GCE) for the electrochemical investigations towards CQT detection. The results indicated that the rGO@AgWO4 /GCE possessed an excellent catalytic activity with a wide linear detection range 1–1108 μM coupled with an ultrasensitive limit of detection (LOD) 0.0661 μM for electrochemical CQT detection. The rGO@AgWO4 /GCE CQT sensor also expressed remarkable sensitivity of 0.6306 μAμM −1 cm −2 in addition to good selectivity and reproducibility. Furthermore, the commercial CQT, river water, tap water and washed vegetable water are used as a representative for real world analysis using rGO@AgWO4 /GCE and results are highly appreciable for the real time CQT detection. Our work proposes a novel hybrid rGO@AgWO4 nanocomposites reinforced electrodes for ultra-trace level CQT detection with good reliability and can be advocated for real time detection of pesticides. Graphical abstract: Image 1 Highlights: Hybrid AgWO4 -rGO nanocomposite is hydrothermally synthesized and used as electrode material. Hazardous crisquat (CQT) is electrochemically detected via AgWO4 -rGO armed electrodes. Electrochemical investigation revealed a wide linear range 1–1108 μM for CQT. Real world studies are done using commercial CQT, tap, river and vegetable washed water.